Development of Interactive Teaching Materials Based on Android Application for Elementary School Students - Aldy Ferdiyansyah; Suhartono Suhartono; Nihayati Nihayati (Universitas Negeri Malang, 2022)
This research aims to produce a prototype of interactive teaching materials based on android applications effectively used in thematic learning in Elementary School. This development research uses the DDD-E model with four stages of development which include: (1) decide, (2) design, (3) develop, and (4) evaluate. The products developed are divided into six applications that focus on the sub-theme of Environmental Conservation. Based on the test results, the obtained paired sample test results had a significance value of 0.001, which is less than 0.05. It can be interpreted that there is a significant difference between student learning outcomes before and after using interactive teaching material. The effectiveness of interactive teaching materials can be seen from the results of the N-Gain test with an average gain score of 0.6, which means the level of effectiveness of interactive teaching materials is in the medium category.